Process evaluation of a parent-child communication intervention for adolescent sexual and reproductive health in Uganda - Danielle Fernandes; Elizabeth Kemigisha; Dorcus Achen; Cecilia Akatukwasa; Gad Ndaruhutse Ruzaaza; Gily Coene; Peter Delobelle; Viola N. Nyakato; Kristien Michielsen (BMC, 2024)
Abstract Background Previous initiatives concerning adolescent sexual and reproductive health (SRH) education in Low-or-Middle Income Countries (LMICs) have been limited by cultural norms and misinformation perpetuated within families. Responding to the paucity of research on the implementation of SRH interventions in LMICs and limited knowledge regarding their mechanisms, this study undertakes a process evaluation of a parent-focused intervention to promote parent-adolescent communication about SRH in Uganda. Methods This paper explores the implementation, contextual factors and mechanisms of impact of the intervention, using the Medical Research Council (MRC) guidelines for process evaluations. Implementation was evaluated through indicators of dose, fidelity and adaptations, acceptability and feasibility. The contextual factors and mechanisms of impact were evaluated to refine the intervention's causal assumptions. Data was collected during April - October 2021 in South-Western Uganda using a mixed-methods approach, including document analysis, intervention observations, interviews, focus group discussions and most significant change stories. Results The acceptability of the intervention was related to its community engagement, the strong rapport with delivery agents, and individual characteristics of participants. Five contextual factors influencing implementation were highlighted; (i) cultural norms, (ii) perceptions about youth SRH, (iii) poverty, (iv) Covid-19 pandemic, and (v) prior research projects in the community. When considering the intervention's mechanisms of impact, four causal pathways were identified; (i) Awareness of SRH needs helped parents overcome stigma, (ii) Parenting skills training improved SRH communication, (iii) Group learning stimulated shared parenting, and (iv) Group learning improved co-parenting. Conclusion The paper presented three key learnings and corresponding recommendations for future research. Firstly, implementation success was credited to meaningful community engagement which improved acceptability and uptake. Secondly, the complex influences of contextual factors highlighted the need for contextual analysis in research studies to inform intervention design. Finally, this evaluation recognised the interplay between mechanisms of impact and suggested further research consider such combined impacts when designing intervention content.